1997
DOI: 10.1002/(sici)1097-0142(19971201)80:11<2156::aid-cncr16>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of differentiated thyroid carcinoma in children and adolescents with respect to age, gender, and histology

Abstract: with DTC (age range, 3-18 years) was collected from 65 clinical institutions in Germany. Characteristics of 80 females and 34 males were evaluated and the influ-1 Clinic for Nuclear Medicine and Tumor Center ence of age, gender, histology, multicentric growth, tumor stage, and lymph node University of Würzburg, Würzburg, Germany. involvement on distant metastases was tested using multivariate discriminant anal-2 Clinic for Pediatrics, University of Lübeck, Lü-ysis. Comparison between groups was performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
0
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 29 publications
10
65
0
8
Order By: Relevance
“…Whereas in prepubertal girls and boys (rare), thyroid cancer is roughly equally represented, with the onset of puberty the incidence increases in females by up to 14 times (Farahati et al 1997). After menopause, the incidence decreases again (Li et al 2013).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Whereas in prepubertal girls and boys (rare), thyroid cancer is roughly equally represented, with the onset of puberty the incidence increases in females by up to 14 times (Farahati et al 1997). After menopause, the incidence decreases again (Li et al 2013).…”
Section: Introductionmentioning
confidence: 83%
“…Certainly, epidemiological and clinical studies demonstrated a three to four times higher prevalence of differentiated thyroid cancer in females than in males and an increase in the incidence of this tumor with the onset of puberty in females is well documented (Farahati et al 1997, Dean & Gharib 2008, Li et al 2013. Furthermore, there is some recent evidence for the progression of papillary microcarcinoma during pregnancy and a higher recurrence rate of thyroid cancer due to pregnancy (Messuti et al 2014, Shindo et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, no common genetic variants in sex hormone pathway genes that may explain the higher incidence rates of proliferative thyroid diseases in females have been detected yet (Schonfeld et al 2012). Another argument for a pathogenetic role of oestrogen is the increasing incidence of differentiated thyroid cancer in females but not in males with the onset of puberty and the simultaneous rise in the levels of sex hormones (Farahati et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Enomoto et al (16) studied 142 pediatric patients with DTC, with a median follow-up of 22 y, and reported that an age of less than 16 y was a risk factor for recurrent disease, in addition to a familial history of thyroid cancer, tumor size, large lymph node metastases, extranodal invasion, and initial distant metastases. Other authors have reported that younger children have a higher risk of relapse (25)(26)(27). In the present study, patients in group 1 (,10 y old) had the worst prognosis; all relapsed.…”
Section: Discussionmentioning
confidence: 99%